2021
DOI: 10.18421/tem103-35
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Self-Regulated Learning Skills in Senior High School Students: A Phenomenological Study

Abstract: The purpose of this research is to analyze self-regulated learning (SRL) level of senior high school students. This research is qualitative research with a phenomenological approach. The research sample consisted of 21 high school students who were selected using purposive sampling technique. Data collection techniques are used in-depth interviews to reveal participant experiences related to SRL. Data analysis techniques are done by using Creswell's analysis model that uses the stages of data collection, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(23 reference statements)
0
7
0
1
Order By: Relevance
“…Davies-Bouldin Index (DBI) diperkenalkan oleh David L. Davies dan Donald W. Bouldin adalah sebuah metode untuk mengevaluasi algoritma pengelompokkan. Davies-Bouldin Index memiliki skema evaluasi internal cluster, dimana baik atau tidaknya hasil cluster dapat dilihat dari kuantitas dan kedekatan antara data hasil cluster [12].…”
Section: Davies-bouldin Index (Dbi)unclassified
“…Davies-Bouldin Index (DBI) diperkenalkan oleh David L. Davies dan Donald W. Bouldin adalah sebuah metode untuk mengevaluasi algoritma pengelompokkan. Davies-Bouldin Index memiliki skema evaluasi internal cluster, dimana baik atau tidaknya hasil cluster dapat dilihat dari kuantitas dan kedekatan antara data hasil cluster [12].…”
Section: Davies-bouldin Index (Dbi)unclassified
“…It is clear from students' comments found in Appendix B that the guided self-paced learning approach and multiple learning modalities employed in the program were beneficial for students. Furthermore, because students were given time in the schedule to reflect and explore the topics further, students had the opportunity to engage in aspects of self-regulated learning related to goal setting, resource gathering, self-reflection, and evaluating their knowledge and limitations (Greene et al, 2015;Kesuma et al, 2021;Robinson and Persky, 2020).…”
Section: How Moving Online May Address Barriers To Participationmentioning
confidence: 99%
“…Furthermore, correlational research has demonstrated that particular SRL techniques are followed by metacognition, help-seeking, and study/time management as being favourably associated to accomplishment and GPA. (Kesuma et al, 2021).…”
Section: Srl and Performancementioning
confidence: 99%
“…Learning is considered a complex interactive process which includes both cognitive, motivation and emotions, which are also the key elements of SRL. Secondary students go through distinct stages of cognitive and mental development than elementary children since they have transitioned into adolescence and can already think critically and abstractly (Kesuma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%